THE TEACHING OF SOLID GEOMETRY FROM THE PERSPECTIVE OF AMAZONIAN CONTEXTUALIZATION: A KIT OF MANIPULATIVE AND DIGITAL ACTIVITIES FOR ELEMENTARY EDUCATION - dos Santos, Carlos Alberto Carvalho; Fernandes, Vera Maria Jarcovis; Schimiguel, Juliano; da Cruz, Keyte Rocha; Mendonça, Deiverson Iamute (Seven Editora, 2026)
This article presents a proposal for pedagogical intervention in the teaching of Solid Geometry for the 8th grade of Elementary Education through a kit of manipulative and digital activities. The initiative arises from the need to address students’ recurring difficulties with three-dimensional concepts, as identified by the Amazonas Learning Verification Assessment (AVAM). The kit, composed of ten activities, integrates low-cost concrete resources and digital tools accessible through QR Codes, promoting active learning contextualized to the Amazonian reality. Grounded in Van Hiele’s Theory of Geometric Thinking Levels and Ausubel’s Theory of Meaningful Learning, the material seeks to develop visualization skills, logical reasoning, and geometric argumentation, in alignment with the National Common Curricular Base (BNCC). Although the educational product has not been empirically applied, its theoretical and methodological design offers an innovative and adaptable resource for educators, with the potential to transform the teaching of Solid Geometry, making it more dynamic, inclusive, and meaningful for students in the region. Regional contextualization is a central pillar, connecting geometric solids to elements of everyday Amazonian life in order to create meaningful learning anchors. This work aims to contribute to improving students’ performance in external assessments and to inspire the development of analogous teaching materials.